Shikonin Attenuates Hepatic Steatosis by Enhancing Beta Oxidation and Energy Expenditure via AMPK Activation - Gwon, So Young (Nutrients, 2020)
Shikonin, a natural plant pigment, is known to have anti-obesity activity and to improve insulin sensitivity. This study aimed to examine the effect of shikonin on hepatic steatosis, focusing on the AMP-activated protein kinase (AMPK) and energy expenditure in Hepa 1-6 cells and in high-fat fed mice. Shikonin increased AMPK phosphorylation in a dose- and time-dependent manner, and inhibition of AMPK with compound C inhibited this activation. In an oleic acid-induced steatosis model in hepatocytes, shikonin suppressed oleic acid-induced lipid accumulation, increased AMPK phosphorylation, suppressed the expression of lipogenic genes, and stimulated fatty acid oxidation-related genes. Shikonin administration for four weeks decreased body weight gain and the accumulation of lipid droplets in the liver of high-fat fed mice. Furthermore, shikonin promoted energy expenditure by activating fatty acid oxidation. In addition, shikonin increased the expression of PPARγ coactivator-1α (PGC-1α), carnitine palmitoyltransferase-1 (CPT1) and other mitochondrial function-related genes. These results suggest that shikonin attenuated a high fat diet-induced nonalcoholic fatty liver disease by stimulating fatty acid oxidation and energy expenditure via AMPK activation.